The role of complement in kidney disease - Petr, Vojtech; Thurman, Joshua M (Nature reviews. Nephrology, 2023)
The complement cascade comprises soluble and cell surface proteins and is an important arm of the innate immune system. Once activated, the complement system rapidly generates large quantities of protein fragments that are potent mediators of inflammatory, vasoactive and metabolic responses. Although complement is crucial to host defence and homeostasis, its inappropriate or uncontrolled activation can also drive tissue injury. For example, the complement system has been known for more than 50 years to be activated by glomerular immune complexes and to contribute to autoimmune kidney disease. Notably, the latest research shows that complement is also activated in kidney diseases that are not traditionally thought of as immune-mediated, including haemolytic-uraemic syndrome, diabetic kidney disease and focal segmental glomerulosclerosis. Several complement-targeted drugs have been approved for the treatment of kidney disease, and additional anti-complement agents are being investigated in clinical trials. These drugs are categorically different from other immunosuppressive agents and target pathological processes that are not effectively inhibited by other classes of immunosuppressants. The development of these new drugs might therefore have considerable benefits in the treatment of kidney disease.
Keywords: aktivace komplementu; autoimunitní nemoci; Kidney Diseases; Kidney; Humans; lidé; nemoci ledvin; Complement System Proteins; komplement; Kidney Glomerulus; glomerulus; Autoimmune Diseases; ledviny; Complement Activation